Guiding Training In Gym Application For Beginner Based On Android Mobile - , Riyad, Bana Handaga, S.T.,M.T.,P.h.D (2016)
Gym is becoming the most favorite place to exercise physic. The most common reason go to the gym is fills self-confidence up to the brim with building muscles throughout the body, but most did not last long then stop doing workout. Unfamiliar with the equipment, poor knowledge about training program and diet program are the main problems. In another case android is the world's most popular mobile platform providing Android Studio where someone can setup a new Android project for different types of Android apps within seconds. Then, created an application guiding training in gym based on android mobile use Android Studio with Java programming language, XML and Database sqlite. This application is offline application, having one level equipped with animation video and alert notification. User must input name, weight, height, and password. Weight and height will determine user are in bulking program or cutting program based on body mass index calculation. The application has been tested on some beginners in gym and the result show that our application got appreciation with the average percent reached 86,8% of five aspects was asked with another word the application can be deployed easily and can solve problems.